Development of a parenting support program to prevent abuse of adolescents in South Africa: findings from a pilot pre-post study - Cluver, L; Lachman, J; Ward, C; Gardner, F; Peterson, T; Hutchings, J; Mikton, C; Meinck, F; Tsoanyane, S; Doubt, J; Boyes, M; Redfern, A (SAGE Publications, 2016)
Purpose: Violence against children increases in adolescence, but there is a research and practice gap in research-supported child abuse prevention for the adolescent years. A pilot programme for low-resource settings was developed in collaboration with NGOs, government and academics in South Africa, using research-supported principles. Methods: This study used a pre-post design to test initial effects of a 10-session parenting programme with 60 participants (30 caregiver-adolescent dyads) in high-poverty rural South Africa. Areas requiring further testing and adaptation were also identified. Results: Pre-post findings show medium to large programme effects in reducing child abuse and adolescent problem behaviour, as well as large effects in improvements of positive parenting, and perceived parent and adolescent social support. Discussion: There is potential to reduce child abuse, improve parenting, and reduce adolescent problem behaviour in rural South Africa through parenting programmes. Further development, testing and longer-term follow-up are required to ascertain potential for scale-up.